Die Ökonomisierung des Krankenhauses Eine Studie über den Wandel pflegerischer Arbeit - Mohan, Robin (Sozialtheorie, 2018)
The transformation of hospitals into companies is repeatedly negotiated as a consistent rationalization strategy. From a sociological perspective, on the other hand, it becomes clear that the much-discussed ¼-economization½ of hospitals is a contradictory process. Robin Mohan traces the history of the hospital through a social theory of economization based on Marx, Weber and Bourdieu, which raises the contradiction between utility value and exchange value as the connecting leitmotiv. The analysis is supplemented by a sociology of labor study, which reconstructs how the economization processes are viewed from the point of view of the nursing staff.